2020
DOI: 10.1002/qre.2777
|View full text |Cite
|
Sign up to set email alerts
|

Improving Shewhart control chart performance for monitoring the Weibull mean

Abstract: In this paper, we are interested in monitoring the stability of a Weibull process mean. We introduce a simplified variable sample size (SVSS) procedure, which consists of using alternately sample sizes nA and nB with nA>nB, to improve the performance of the traditional X¯ control chart (a fixed sample size n). Operationally, the proposal is relatively simple and its adoption yields a faster signal of an abnormal situation compared with the traditional X¯ chart in a variety of shifts. We present instructions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In this section, the procedure to improve (in terms of 𝐴𝑅𝐿) the attribute control charts X𝑡𝑛 and 𝑆 2 𝑡𝑛 is described. It follows closely to the one proposed by Ho et al 26 The main idea is the switch between two sample sizes 𝑛 𝑎 and 𝑛 𝑏 (𝑛 𝑎 > 𝑛 𝑏 ) sequentially taken in the inspection operation. Hereon they will be named respectively as "Improved X𝑡𝑛 " and "Improved 𝑆 2 𝑡𝑛 " attribute control charts and, respectively, denoted as X𝑡𝑛(𝐼) and 𝑆 2 𝑡𝑛(𝐼) .…”
Section: 𝒕𝒏mentioning
confidence: 86%
See 2 more Smart Citations
“…In this section, the procedure to improve (in terms of 𝐴𝑅𝐿) the attribute control charts X𝑡𝑛 and 𝑆 2 𝑡𝑛 is described. It follows closely to the one proposed by Ho et al 26 The main idea is the switch between two sample sizes 𝑛 𝑎 and 𝑛 𝑏 (𝑛 𝑎 > 𝑛 𝑏 ) sequentially taken in the inspection operation. Hereon they will be named respectively as "Improved X𝑡𝑛 " and "Improved 𝑆 2 𝑡𝑛 " attribute control charts and, respectively, denoted as X𝑡𝑛(𝐼) and 𝑆 2 𝑡𝑛(𝐼) .…”
Section: 𝒕𝒏mentioning
confidence: 86%
“…25 This article proposes a procedure to improve the performance for the X𝑡𝑛 control chart (and 𝑆 2 𝑡𝑛 control chart). It is based on a simplified variable sample size scheme introduced by Ho et al, 26 which makes sequential switches between two sample sizes 𝑛 𝑎 and 𝑛 𝑏 (with 𝑛 𝑎 > 𝑛 𝑏 ) and checking whether the sample average of the 𝑛 𝑎 (or 𝑛 𝑏 ) simulated values from truncated normal distributions exceeds the control limits or not. In Ho et al, 26 the procedure was used for monitoring the Weibull mean and demonstrated a reasonable reduction in ARL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performances were compared in terms of 𝐴𝑅𝐿 in scenarios of shift sizes (𝛿) in the process mean. This same scheme of inspection was previously studied by Ho et al 14 to improve the performance of 𝑋 control chart to monitor a Weibull mean. The design simplifies the decision-making, because it is a predetermined fixed sequence, facilitates its operation, minimizes the need for specialized training, and can reduce the possibility of errors in the elaboration of the control chart and, consequently, the decision-making in the long term.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, Ho et al 33 . proposed a simplified variable sample size (SVSS) procedure to improve the X¯std$\overline{X}_{{\rm std}}$ for the Weibull mean.…”
Section: Performance Of the X¯$\overline{x}$ Control Chart With Klein...mentioning
confidence: 99%